Hubungan Self Disclosure dengan Kepercayaan Diri Siswa dalam Mengemukakan Pendapat di Depan Kelas - Ade Nofembri; Linda Fitria; Popi Radyuli (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2021)
This research is motivated by the low self-confidence of students in expressing opinions in front of the class. One of the reasons is the low self-disclosure of students. This study aims to see a picture of self-confidence, self-disclosure, and to examine the relationship between students' self-disclosure and self-confidence in expressing opinions in front of the class. The research method used is descriptive and correlational approaches. The study population was the tenth grade students, amounting to 455 people. With a sample of 204 people, who were selected by purposive sample technique. Data were analyzed using percentage techniques and to see the relationship between the two variables using Pearson Correlation Product Moment. The results of the study were found (1) in general students 'self-confidence was in the medium category, (2) in general students' selfdisclosure was in the medium category, and (3) there was a significant relationship between self-disclosure and student self-confidence with rxy = 0.415 and level significance of 0.000. Based on the findings of this study, it can be a reference for students about the importance of increasing self-disclosure so that students' confidence in expressing opinions in front of the class increases. In addition, guidance and counseling teachers can provide counseling services based on the findings of this study.